Pathogenesis of acute lung injury of the newborns - YANG Ruotong, ZHAO Guoying, WANG Hao (Jichu yixue yu linchuang)
Due to factors such as narrow airways and incomplete development of alveoli, newborns are prone to acute lung injury (ALI), which may progress to severe condition known as acute respiratory distress syndrome (ARDS). The mechanisms underlying the occurrence and progression of ALI in newborns involve various aspects, including oxidative stress, iron death, inflammatory response and reduction of pulmonary surfactant. Further research into these mechanisms is expected to provide strategy to guide clinical management in novo pathway.